Pengaruh Terhadap Firm Size, Financial Distress, dan Financial Performance terhadap Tax Avoidance pada Perusahaan Energi di Indonesia - Tommy setiawan; Muhammad Ridwan (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
The research time period used is 5 years, namely the 2018-2022 period. The population of this study includes all energy companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2022 period. The sampling technique used purposive sampling technique. Based on the predetermined criteria, 11 companies were obtained. The type of data used was secondary data obtained from the Indonesia Stock Exchange website. The analytical method used is panel data regression analysis and tested using the Eviews version 9.0 program. The results show that firm size has an effect on tax avoidance, financial distress has no effect on tax avoidance, and financial performance has no effect on tax avoidance. Simultaneously that firm size, financian distress and financial performance has an effect on tax avoidance.